Pengembangan Nilai-Nilai Filosofi Sawung Blanggreng Sebagai Upaya Penerapan Growth Mindset Untuk Meningkatkan Motivasi Belajar Siswa - Setiyawati, Ririn; Isriyah, Mudafiatun; Fauziyah, Nailul (Educatio, 2026)
This study aims to develop a counseling guidance module based on the philosophical values of the traditional dance Sawung Blanggreng as a medium for implementing a growth mindset to improve students’ learning motivation at SMK Trunojoyo Jember. The background of this research stems from the problem of low learning motivation caused by the dominance of a fixed mindset among students, which makes them tend to give up easily when facing academic challenges. To address this issue, the study integrates the noble values of Sawung Blanggreng, which are rich in me$ning—courage, perseverance, togetherness, spirituality, and discipline— deemed in line with the spirit of the growth mindset. The research method employed was Research and Development (R&D) using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) and a mixed- method approach that combined qualitative data obtained through interviews, observations, and expert validation with quantitative data derive$d from pre-test and post-test results. The product developed was a counseling guidance module and a learning model called “Sawung Aktif Berkarakter,” validated by material experts, media experts, and teachers, with results showing a “valid” category (70%–80%), thus deemed feasible for use in learning prior to limited implementation with eleventh-grade students. The results of the paired sample t-test showed a significant improvement with a significance value of 0.027 (<0.05), indicated by an increase in the students’ mean score from 74.74 to 77.43. These findings prove that the integration of Sawung Blanggreng values is effective in fostering a growth mindset while simultaneously enhancing students’ learning motivation.